Exploring the influence of the home literacy environment on early literacy and vocabulary skills in Korean–English bilingual children - Kim, Wi-Jiwoon; Yim, Dongsun (Frontiers in Psychology, 2024)
Studies have emphasized the significance of maintaining a heritage language for various reasons such as the establishment of linguistic and cultural identity, as well as socio-emotional development. Despite the crucial role that literacy development in a heritage language plays in language preservation, there is a scant research that explores the impact of home literacy environment and literacy development in children with a heritage language. This study aimed to examine the home literacy environment and literacy-related skills in 4-to 5-year-old Korean–English bilingual children living in an English-speaking country, Australia, whose heritage language is Korean, and to investigate the relationships among the home literacy environment factors and the child-internal literacy-related skills. The study employed parental questionnaires and video analyses of parent–child shared book reading sessions to assess the Korean and English home literacy environment. Children’s early literacy skills in Korean and English, along with their Korean, English, and conceptual vocabulary skills, were measured as literacy-related skills. The findings indicated that parents utilized an indirect approach for Korean literacy practices, in contrast to a more direct and explicit method for English literacy practices. However, active and direct literacy practices were found to be essential for Korean early literacy development, while indirect methods are sufficient for English early literacy skills. Moreover, the availability of abundant Korean literacy resources at home had a positive impact on the development of Korean and English, as well as conceptual vocabulary skills. In conclusion, this study underscores the importance of providing a robust literacy environment in a heritage language in bilingual families to promote language proficiency in both the heritage language and the dominant social language, while also supporting the development of conceptual language skills.